Social Marketing dalam Pendampingan Optimalisasi Komunikasi Digital Kesiapsiagaan Bencana di Dinas Penanggulangan Kebakaran dan Penyelamatan Pemerintah Provinsi DKI Jakarta - Hilarius Bambang Winarko (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study analyzes the effectiveness of social marketing-based digital communication assistance in improving the capacity of 32 Jakarta Fire Department employees for disaster preparedness. The method used was participatory through training, social marketing strategy assistance, digital content development, and emergency simulations. Evaluation using questionnaires and observations showed an increase in participant understanding (average educational value of 3.63 on a scale of 4). Participants were able to develop disaster content that was more structured, informative, and in line with digital trends. All respondents (100%) stated that the activity was beneficial. The main challenges were the habit of one-way communication and the minimal use of micro-content (TikTok, Instagram Reels). This model can be replicated by other disaster agencies in Indonesia. Sustainable mentoring and integration of social marketing into the Fire Department's public communication SOP are needed. This study integrates social marketing (4Ps extended mix) with trend-jacking and a humanizing first responder approach in digital disaster communication in local government.